Revisiting Antagonist Effects in Hypoglossal Nucleus: Brainstem Circuit for the State-Dependent Control of Hypoglossal Motoneurons: A Hypothesis - Fenik, Victor B. (Frontiers in Neurology, 2015)
We reassessed and provided new insights into the findings that were obtained in our previous experiments that employed the injections of combined adrenergic, serotonergic, GABAergic and glycinergic antagonists into the hypoglossal nucleus in order to pharmacologically abolish the depression of hypoglossal nerve activity that occurred during carbachol-induced REM sleep-like state in anesthetized rats. We concluded that noradrenergic disfacilitation is the major mechanism that is responsible for approximately 90% of the depression of hypoglossal motoneurons whereas the remaining 10% can be explained by serotonergic mechanisms that have net inhibitory effect on hypoglossal nerve activity during REM sleep-like state. We hypothesized that both noradrenergic and serotonergic state-dependent mechanisms indirectly control hypoglossal motoneuron excitability during REM sleep; their activity are integrated and mediated to hypoglossal motoneurons by reticular formation neurons. In addition, we proposed a brainstem neural circuit that can explain the new findings.